Ecologia de mosquitos (Diptera: Culicidae) em áreas do Parque Nacional da Serra da Bocaina, Brasil.I - Distribuição por habitat Ecology of mosquitoes (Diptera: Culicidae) in areas of Serra da Bocaina National Park, Brazil. I - Habitat distribution - Anthony Érico Guimarães; Carla Gentile; Catarina M Lopes; Alessandro Sant'Anna; Alexandre M Jovita (Universidade de São Paulo, 2000)
OBJETIVO: Estabelecer a influência exercida por três diferentes biótopos em áreas do Parque Nacional da Serra da Bocaina (PNSB) sobre a fauna local de mosquitos. MÉTODOS: Foram realizadas capturas mensais em ambiente silvestre e domiciliar, em isca humana, durante três diferentes períodos do dia, pelo período de 24 meses consecutivos, de janeiro de 1991 a dezembro de 1992. RESULTADOS: Foram capturados 11.808 espécimes adultos, pertencentes a 28 espécies. Ru. reversa e An. cruzii foram predominantes, respectivamente 52,5% e 17,9% do total de mosquitos. Ru. reversa representou 59,4% do total de espécimes no ambiente de mata fechada, seguida por Ru. frontosa com 10,5% e An. cruzii com 9,9%. No ambiente formado por campos de altitude e matas de galeria, o An. cruzii predominou com 48,1%, seguido por Ru. reversa com 28,1%. No ambiente modificado pelo homem, o An. cruzii predominou com 73,7% dos espécimes. Coquillettidia chrysonotum foi a única que se apresentou preferencialmente nesse biótopo: 14,9% no intra, 19,4% no peri e 65,7% no extradomicílio. An. cruzii e Ru. reversa foram constantes em todos os ambientes ao longo do ano. CONCLUSÕES: Com exceção de Cq. chrysonotum, com preferência pelo ambiente modificado pelo homem, os mosquitos apresentam hábitos assinantrópicos no PNSB. An. cruzii, embora assinantrópico, se aproxima e adentra o domicílio para realizar a hematofagia. A presença do Ae. serratus no extra e peridomicílio reforça a importância epidemiológica como vetora potencial de arboviroses. Os Sabethini apresentaram-se exclusivamente silvestres. OBJECTIVE: To assess the mosquito fauna in Serra da Bocaina National Park (PNSB), by collecting information through a general survey, and investigating the population behavior in habitats within the park with different vegetation. METHODS: Human bait collections were conducted once a month for both the forest and households, in diurnal and nocturnal periods, three time a day, throughout 24 months, from January 1991 to December 1992. RESULTS: A total of 11,808 adult mosquitoes belonging to 28 species were collected. Runchomyia reversa and Anopheles cruzii were the most abundant, reaching 52.5% and 17.9% of the total collected specimens, respectively. In the dense forest, Ru. reversa comprised 59.4% of the total, followed by Ru. frontosa with 10.5%, and An. cruzii with 9.9%. In the high altitude fields and in gallery forest, An. cruzii was the most abundant (48.1%) followed by Ru. reversa (28.1%). Inside households An. cruzii was also the most prominent species, representing 73.7% of the total for that location. Coquillettidia chrysonotum was the only species mainly seen in the household surroundings, where its distribution was: 14.9% (indoors), 19.4% (close to the house), and 65.7% (outdoors). An. cruzii and Ru. reversa were found throughout the whole year and captured every month. CONCLUSIONS: Mosquitoes in PNSB present an assynanthropic behavior, except for Cq. chrysonotum which lives preferentially in the household environment. Though An. cruzii is an assynantropic species it may approaches live near households and even invades and infest them for the blood meals. The occurrence of Aedes serratus in the household vicinity emphasizes its epidemiological importance as a potential vector of arboviruses. Sabethini are all exclusively sylvatic species.